Stable isotopic evidence for increased terrestrial productivity through geological time - Gregory J. Retallack; Ilya N. Bindeman (Scientific Reports)
Abstract Marine life on Earth is known back to the Archean Eon, when life on land is assumed to have been less pervasive than now. Precambrian life on land can now be tested with stable isotopes because living soil CO2 is isotopically distinct for both carbon and oxygen from both marine and volcanic CO2. Our novel compilation of previously published oxygen and carbon isotopic compositions of pedogenic and paleokarst carbonate can be compared with the coeval marine record. Long-term enrichment (to heavier isotopic composition) of oxygen, but no significant trend in carbon through time, long apparent from marine carbonate, is now demonstrated also for pedogenic and paleokarst carbonate. Oxygen isotopic enrichment is not due to changing global temperature or hypsometry, but to increased evapotranspiration and photosynthesis on larger continents. Differences in isotopic composition between land and sea have increased in an episodic fashion, peaking at times of major evolutionary innovations for life on land, and also at times of ice ages. The δ13C and δ18O divergences between land and sea correspond to terrestrial productivity spikes including evolution of Neoproterozoic (635 Ma) lichens, middle Ordovician (470 Ma) non-vascular land plants, middle Devonian (385 Ma) forests, early Cretaceous (125 Ma) angiosperms, and middle Miocene (20 Ma) sod grasslands.